Earthquake Risk in Multifamily Residential Buildings : Europe and Central Asia Region - World Bank Group (World Bank, Washington, DC, 2020)
Multifamily residential buildings in earthquake-prone cities across Central Europe, Balkans, and Central Asia have proved to be vulnerable and have revealed several structural deficiencies during previous earthquake events. Earthquakes in these regions have damaged certain types of multifamily buildings beyond repair or have caused complete collapse, resulting in extensive homelessness and many fatalities. The vulnerability of some of these buildings can be attributed to the mass-produced nature of multifamily residential buildings as well as lack of maintenance, oversight, and disinvestment over many decades. This study investigates earthquake risk of multifamily buildings constructed before 2000 across cities in countries within Europe and Central Asia (ECA) to better understand their behavior and potential losses when subjected to earthquakes, and to inform recommendations for mitigation.